High-affinity binding of the Drosophila Numb phosphotyrosine-binding domain to peptides containing a Gly-Pro-(p)Tyr motif - Li, Shun-Cheng (The National Academy of Sciences of the USA, 1997)
The phosphotyrosine-binding (PTB) domain is a recently identified protein module that has been characterized as binding to phosphopeptides containing an NPXpY motif (X = any amino acid). We describe here a novel peptide sequence recognized by the PTB domain from Drosophila Numb (dNumb), a protein involved in cell fate determination and asymmetric cell division during the development of the Drosophila nervous system. Using a Tyr-oriented peptide library to screen for ligands, the dNumb PTB domain was found to bind selectively to peptides containing a YIGPYφ motif (φ represents a hydrophobic residue). A synthetic peptide containing this sequence bound specifically to the isolated dNumb PTB domain in solution with a dissociation constant (K(d)) of 5.78 ± 0.74 μM. Interestingly, the affinity of this peptide for the dNumb PTB domain was increased (K(d) = 1.41 ± 0.10 μM) when the second tyrosine in the sequence was phosphorylated. Amino acid substitution studies of the phosphopeptide demonstrated that a core motif of sequence GP(p)Y is required for high-affinity binding to the dNumb PTB domain. Nuclear magnetic resonance experiments performed on isotopically labeled protein complexed with either Tyr- or pTyr-containing peptides suggest that the same set of amino acids in the dNumb PTB domain is involved in binding both phosphorylated and nonphosphorylated forms of the peptide. The in vitro selectivity of the dNumb PTB domain is therefore markedly different from those of the Shc and IRS-1 PTB domains, in that it interacts preferentially with a GP(p)Y motif, rather than NPXpY, and does not absolutely require ligand phosphorylation for binding. Our results suggest that the PTB domain is a versatile protein module, capable of exhibiting varied binding specificities.